2021
DOI: 10.1088/1755-1315/902/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of female swamp buffalo reared under Kalang production system in South Kalimantan

Abstract: Swamp buffalo has been an integral component of society in the swamp area in South Kalimantan. The system is characterized by 2-5 farmers rearing herds semi intensively in one shared kalang, a traditional wooden shelter on swamp area. This study was aimed to determine the reproductive characteristics of female swamp buffalo under kalang systems in Hulu Sungai Selatan Regency, The Province of South Kalimantan. The data of reproductive characteristics and farming systems were collected through interviewing 21 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…Kerbau pada Desa Pulau Lanting, memiliki calving interval sebesar 13,61±0,98. Nilai jarak beranak tersebut lebih baik jika dibandingkan oleh beberapa penelitian kerbau rawa lain seperti pada daerah Kalimantan Selatan yaitu 16,5±0,15 bulan [12], pada Sumatera Barat yaitu 27,26±8,84 bulan [17], dan pada Kabupaten Aceh Barat yaitu 18,14 bulan [18]. Angka tersebut namun tidak begitu jauh dibandingkan wilayah muara muntai yaitu 13 bulan [11].…”
Section: Masa Kosong Atau Days Open Kerbau DI Desa Pulauunclassified
See 1 more Smart Citation
“…Kerbau pada Desa Pulau Lanting, memiliki calving interval sebesar 13,61±0,98. Nilai jarak beranak tersebut lebih baik jika dibandingkan oleh beberapa penelitian kerbau rawa lain seperti pada daerah Kalimantan Selatan yaitu 16,5±0,15 bulan [12], pada Sumatera Barat yaitu 27,26±8,84 bulan [17], dan pada Kabupaten Aceh Barat yaitu 18,14 bulan [18]. Angka tersebut namun tidak begitu jauh dibandingkan wilayah muara muntai yaitu 13 bulan [11].…”
Section: Masa Kosong Atau Days Open Kerbau DI Desa Pulauunclassified
“…Umur kawin pertama tersebut terbilang lebih lama dibandingkan umur kawin pertama kerbau rawa di Kecamatan Malang dan kerbau lumpur pada Kabupaten Cianjur yaitu 29,17±13,77 [10] bulan dan 26,6±6,96 [11] bulan. Namun apabila dibandingkan dengan kerbau rawa dengan sistem pemeliharaan yang hampir sama yaitu pada daerah Kalimantan Selatan [12] umur kawin pertama kerbau pada daerah pulau lanting 16,5 bulan jauh lebih cepat. Faktor keterlambatan umur kawin pertama yang terjadi dengan sistem pemeliharaan ekstensif seperti pada Desa Pulau Lanting adalah kebutuhan nutrisi yang belum mencukupi dengan baik untuk kerbau bereproduksi secara optimal.…”
unclassified
“…In addition, buffalo calves that are not yet strong enough to swim in search of feed will be left behind and experience a lack of feed, especially buffalo calves that are still lactating. This is suspected to cause high mortality in buffalo calves and adversely affect the buffalo's reproductive performance [5].…”
Section: Seasonal Native Grass Productionmentioning
confidence: 99%
“…Other research reported there are declines in the availability and productivity of native grasses species that are palatable for buffalo. These resulted in high mortality of buffalo calves due to lack of feed, especially in the deep water season [5]. In addition, the buffalo's body weight decreased even though the physical measurements were not significantly different from the previous report, where this was suspected because of a lack of feed intake and nutrition [1].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation